Literature Analysis of Tafsīr Tarbawiy (Qur’anic Educational Interpretation) from Paul Ricoeur’s Hermeneutic Perspective and Its Relevance as A Source of Islamic Education - Rosidin Rosidin; Fenty Andriani (SUHUF, 2022)
This paper analyzes nine tafsīr tarbawiy (Quranic educational interpretation) literatures in Indonesia from Ricoeur’s hermeneutics perspective. There are two main research findings. First, as objective pole, tafsīr tarbawiy terminology meaning structure as Qur’anic educational interpretation written by Islamic experts for pragmatic and idealistic purposes. As subjective pole, tafsīr tarbawiy literature discussing Islamic education by quoting educational verses through the thematic interpretation (mauḍūʻī) method using various references, according to the author’s subjectivity. There are strengths and limitations of tafsīr tarbawiy literature. The strength is it opens the way for construction of tafsīr tarbawiy literature which is solutive and realistic. The limitation is its interpretation is ideological and utopian. Second, tafsīr tarbawiy literature is relevant as a source of Islamic education theory and practice since it is prepared for pragmatic purposes as a reference for tafsīr tarbawiy course, written by the Islamic education theorists and practitioners, and contains a thick discussion on issues of Islamic education, though the quality and validity are graded, based on the competence level which is the author’s appropriation.